2020
DOI: 10.1038/s41598-020-62242-1
|View full text |Cite
|
Sign up to set email alerts
|

Iodine and bromine in fish consumed by indigenous peoples of the Russian Arctic

Abstract: Fish muscle may constitute one of the main sources of iodine (I) for the indigenous peoples of the Russian Arctic, although limited information is available about its content in commonly consumed fish species. In the current study, bromine (Br), I, the essential elements (copper, selenium and zinc) and other non-essential elements-specifically mercury, arsenic (As), cadmium, lead and nickel-have been quantified in 10 fish species consumed by people living in the Nenets and Chukotka Regions. Fish muscle was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The Br:I ratio reached 2.66 in LAR. This ratio should be kept low to prevent goitrogenic effects derived from excess bromine [ 47 ]. However, it is known that Br is also an essential nutrient due to its requirements for collagen IV formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Br:I ratio reached 2.66 in LAR. This ratio should be kept low to prevent goitrogenic effects derived from excess bromine [ 47 ]. However, it is known that Br is also an essential nutrient due to its requirements for collagen IV formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the calculated amount of seafood consumed per day and the concentration of the elements in breast milk was examined; correlations were found with Hg (0.531), Br (0.463), Se (0.409), and As (0.375). These four elements are elements typical of those contained in seafood [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) reports that about 1.6 billion individuals are at risk of iodine deficiency diseases worldwide (WHO, 2004).The main iodine supply occurs via nutrition and seafood is the most important natural source containing a relatively large amount of iodine (Eckhoff and Maage, 1997). Many researches on the iodine content of various fish species from different countries have shown that the accumulation of iodine in fish from different aquatic resources differs from species to species and often depends on the type of the species, environmental conditions, or can vary seasonally (Ansari et al, 2010 andSobolev et al, 2020).…”
Section: Micro-element Concentrationmentioning
confidence: 99%